-28xy/4
-7xy
Therefore, the first answer is correct.
Hope this helps!
Answer:78phy
gigh[ood9..8d55.5.5.5.5.5.5.5.6.s7s47.4
Step-by-step explanation:
Hello there!
3x - y = 3
-x + y = 3
We need to solve 3x - y = 3 for y
Let start by adding -3x to both sides
3x - y = 3
3x - 3x - y = 3 - 3x
-y = 3 - 3x
We cannot leave the variable with a negative sign. We must multiply both sides by -1
-y * -1= (3 - 3x)-1
y = 3x - 3
Substitute 3x -3 for y in -x+y=3
-x + y = 3
-x + 3x - 3 = 3
2x - 3 = 3
2x = 3 + 3
2x = 6
x = 6/2
x = 3
Now substitute 3 for x in y=3x -3
y = 3x - 3
y = 3(3) - 3
y= 9 - 3
y= 6
Thus,
The answer is x=3 and y=6
It is always my pleasure to help students like you :)
As always, I am here to help!
1kg = 1000g
1000g/5g= 200g
4.40/5 = 0.88
Answer:
A scale copy of a figure is a figure that is geometrically similar to the original figure.
Step-by-step explanation:
Hope this makes sense.